Innovative Cell and Platelet Rich Plasma Therapies for Diabetic Foot Ulcer Treatment: The Allogeneic Approach - Mastrogiacomo, Maddalena; Nardini, Marta; Collina, Maria Chiara; Di Campli, Cristiana; Filaci, Gilberto; Cancedda, Ranieri; Odorisio, Teresa (Frontiers in Bioengineering and Biotechnology, 2022)
Cutaneous chronic wounds are a major global health burden in continuous growth, because of population aging and the higher incidence of chronic diseases, such as diabetes. Different treatments have been proposed: biological, surgical, and physical. However, most of these treatments are palliative and none of them can be considered fully satisfactory. During a spontaneous wound healing, endogenous regeneration mechanisms and resident cell activity are triggered by the released platelet content. Activated stem and progenitor cells are key factors for ulcer healing, and they can be either recruited to the wound site from the tissue itself (resident cells) or from elsewhere. Transplant of skin substitutes, and of stem cells derived from tissues such as bone marrow or adipose tissue, together with platelet-rich plasma (PRP) treatments have been proposed as therapeutic options, and they represent the today most promising tools to promote ulcer healing in diabetes. Although stem cells can directly participate to skin repair, they primarily contribute to the tissue remodeling by releasing biomolecules and microvesicles able to stimulate the endogenous regeneration mechanisms. Stem cells and PRP can be obtained from patients as autologous preparations. However, in the diabetic condition, poor cell number, reduced cell activity or impaired PRP efficacy may limit their use. Administration of allogeneic preparations from healthy and/or younger donors is regarded with increasing interest to overcome such limitation. This review summarizes the results obtained when these innovative treatments were adopted in preclinical animal models of diabetes and in diabetic patients, with a focus on allogeneic preparations.